Yield anomaly in L12 Co3AlxW1−x vis-à-vis Ni3Al. (15th March 2017) - Vamsi, K.V.; Karthikeyan, S.
Abstract: First principles calculations were performed in Co3 Alx W1−x to estimate fault energies, elastic constants and parameters determining the thermodynamic viability and kinetics of yield anomaly. These parameters predict the occurrence of yield anomaly, but only for a limited range of compositions. The driving force for cross-slip resulting in sessile dislocation configurations and cube slip is lower in Co3 Alx W1−x than Ni3 Al due to the less-pronounced anisotropy between antiphase boundary energies on the cube and octahedral planes. Yield anomaly is expected at higher temperatures in Co3 Alx W1−x because of the higher activation energy resulting from the higher shear modulus. Graphical abstract: